Designing of an off-grid Photovoltaic system with battery storage for remote location - Naqvi, Asad A.; Bin Nadeem, Talha; Ali Zaidi, Asad (TECCIENCIA, 2021)
Off-grid Photovoltaic (PV) system along with battery storage is very effective solution for electrification in remote areas. However, battery capacity selection is the most challenging task in system designing. In this study, an off-grid PV system along with battery storage is designed for the remote area of Karachi, Pakistan. The system is designed by considering the maximum energy requirement in summer season. The battery storage is selected to fulfill the energy demand during the night and cloudy seasons. On the basis of load, a total of 6 kW system is required to fulfill the energy demand. For such system, 925 Ah of battery is required to meet the energy requirement for a day in absence of solar irradiation. A regression-based correlation between battery capacity and energy demand is prepared for suitable battery sizing using Minitab. An economic analysis of the project is also carried out from which a net present value and simple payback are determined as USD 10,348 and 3 years, respectively. The environmental benefits are also been determined. It is found that the system will reduce around 7.32 tons of CO2 per annum which corresponds to the 183.69 tons of CO2 not produced in the entire project life.